Konstruksi Fiqh Pluralitas Masyarakat Tradisional: The Construction of Fiqh in the Context of Traditional Plural Societies - Ishaq Ishaq (Fenomena, 2016)
Societal plurality and the dominance of sectarian-exclusive fiqh that neglects justice and local culture are critical issues in contemporary Islamic law. This article employs legal adaptability theory and Abid al-Jabiry's Arab reasoning framework as the main theoretical map to analyze the struggle between the multicultural ushul fiqh paradigm and the traditional literalistic paradigm. The research aims to reveal how plurality fiqh is constructed within the Ma'had Aly Situbondo community. A qualitative descriptive-analytical method with a contemporary intellectual history approach was applied through participant observation, in-depth interviews, and documentation. The findings show that the community's multicultural ushul fiqh paradigm reflects religious utilitarianism, integrating theocentric and anthropocentric dimensions and moving beyond textual meaning toward the ethical and moral substance of the texts. In conclusion, the construction of plurality fiqh in this community is moderate and evolutionary rather than revolutionary, yet it still contains epistemological weaknesses in the form of textual objectivism, which may hinder the realization of emancipatory fiqh. More critical epistemological analysis and methodological tools that integrate text and social reality are recommended. Pluralitas masyarakat dan dominasi fiqh sektarian-eksklusif yang mengabaikan keadilan dan budaya lokal menjadi isu krusial dalam hukum Islam kontemporer. Artikel ini menggunakan peta besar teori adaptibilitas hukum dan kerangka nalar Arab Abid al-Jabiry untuk menganalisis pergulatan antara paradigma ushul fiqh multikultural dengan paradigma tradisional literalistik. Penelitian bertujuan mengungkap konstruksi fiqh pluralitas di komunitas Ma’had Aly Situbondo. Metode kualitatif deskriptif-analitik dengan pendekatan sejarah intelektual kontemporer diterapkan melalui observasi partisipan, wawancara mendalam, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa paradigma ushul fiqh multikultural komunitas ini bercorak utilitarianisme religius yang mensinergikan dimensi teosentris dan antroposentris, serta melampaui makna tekstual menuju substansi etis-moral nash. Kesimpulannya, konstruksi fiqh pluralitas komunitas Ma’had Aly bersifat evolutif moderat, bukan revolutif, namun masih mengandung kelemahan epistemologis berupa objektivisme teks yang berpotensi menghambat terwujudnya fiqh emansipatoris. Diperlukan analisis epistemologis lebih kritis dan perangkat metodologis yang lebih integratif antara teks dan realitas sosial.